2000
DOI: 10.1046/j.1365-2265.2000.01156.x
|View full text |Cite
|
Sign up to set email alerts
|

Goitrogenesis during pregnancy and neonatal hypothyroxinaemia in a borderline iodine sufficient area

Abstract: In a borderline iodine sufficient area, pregnancy posed an important stress resulting in higher rates of maternal goitrogenesis as well as neonatal hypothyroxinaemia and hyperthyro- trophinaemia. An adequate iodization program is necessary to eliminate iodine deficiency disorders during pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
47
1
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 34 publications
8
47
1
1
Order By: Relevance
“…Similar to our results, one study performed in northern Portugal (31) and another from Spain (34) did not find statistical differences in UIC values between early and late pregnancy. However, other authors have referred a clear decrease (43,44), while others have shown even an increase (45). These discrepancies are probably due to the level of iodine intake and other unclear ethnic nutritional differences in the analyzed women (44).…”
Section: Urine Iodine Concentrationmentioning
confidence: 61%
“…Similar to our results, one study performed in northern Portugal (31) and another from Spain (34) did not find statistical differences in UIC values between early and late pregnancy. However, other authors have referred a clear decrease (43,44), while others have shown even an increase (45). These discrepancies are probably due to the level of iodine intake and other unclear ethnic nutritional differences in the analyzed women (44).…”
Section: Urine Iodine Concentrationmentioning
confidence: 61%
“…UI concentrations increased during pregnancy in iodine-replete areas [12][13][14] and in borderline-sufficient areas [12,15] increasing during the course of pregnancy. [12,16].…”
Section: Discussionmentioning
confidence: 99%
“…2 At the same time, studies also reported that one third of local pregnant women were iodine-deficient based on their urinary iodine concentration (UIC), from the first through third trimester. 3,4 Pregnant and lactating women are among the most vulnerable groups in the population as iodine plays an important role in early neuronal migration and maturation in the developing fetus and infants. A local expert panel group was established in 2003 to encourage the monitoring of iodine status and rectify the problem.…”
Section: Implications For Clinical Practice or Policymentioning
confidence: 99%